Addressing feasibility challenges to delivering intradialytic exercise interventions: a theory-informed qualitative study. Issue 3 (20th August 2021) - Castillo, Gisell; Presseau, Justin; Wilson, Mackenzie; Cook, Charles; Field, Bonnie; Garg, Amit X; McIntyre, Christopher; Molnar, Amber O; Hogeterp, Betty; Thornley, Michelle; Thompson, Stephanie; MacRae, Jennifer M; et al.
Abstract: Background: Intradialytic exercise (IDE) may improve physical function and health-related quality of life. However, incorporating IDE into standard hemodialysis care has been slow due to feasibility challenges. We conducted a multicenter qualitative feasibility study to identify potential barriers and enablers to IDE and generate potential solutions to these factors. Methods: We conducted 43 semistructured interviews with healthcare providers and patients across 12 hospitals in Ontario, Canada. We used the Theoretical Domains Framework and directed content analysis to analyze the data. Results: We identified eight relevant domains (knowledge, skills, beliefs about consequences, beliefs about capabilities, environmental context and resources, goals, social/professional role and identity, and social influences) represented by three overarching categories: knowledge, skills and expectations: lack of staff expertise to oversee exercise, uncertainty regarding exercise risks, benefits and patient interest, lack of knowledge regarding exercise eligibility; human, material and logistical resources: staff concerns regarding workload, perception that exercise professionals should supervise IDE, space, equipment and scheduling conflict concerns; and social dynamics of the unit: local champions and patient stories contribute to IDE sustainability. We developed a list of actionable solutions by mapping barriers and enablers to behavior change techniques. We also developed a feasibility checklist of 47 questions identifying key factors to address prior to IDE launch. Conclusions: Evidence-based solutions to identified barriers to and enablers of IDE and a feasibility checklist may help recruit and support units, staff and patients and address key challenges to the delivery of IDE in diverse clinical and research settings.